Comparison of the Plaque Removal and Cleaning Efficiency of Regular and Large-Head Toothbrushes - Ji-won Lee; Myoung-Hee Kim; Koung-hee Kim; Da-bin Han; Yu-jin Hwang; Young Sun Hwang (The Korean Society of Dental Hygiene Science, 2024)
Background: The management of dental plaque and the appropriate use of oral hygiene tools are crucial for oral health. With increasing interest in oral health care, various oral hygiene products are available on the market. As the most basic oral hygiene tool, the large-head toothbrush has gained significant consumer interest. This study evaluates the suitability of large-head toothbrushes as oral hygiene tools by comparing their efficacy with that of regular-sized toothbrushes. Methods: We evaluated the efficacy of large-head and regular-sized toothbrushes. The amount of dental plaque before and after brushing was measured using quantitative light-induced fluorescence digital (QLF-D) images and the plaque index (PI) in adult participants with more than 28 teeth (n=15/group). After brushing, the collected toothbrushes were rinsed 10 times in clean water, thoroughly dried, and weighed on an electronic scale. Data were analyzed using the Wilcoxon signed-rank test with SPSS Statistics Version 29.0. Results: QLF-D analysis showed a significant decrease in fluorescence intensity scores after use of a regular-sized toothbrush, whereas the scores after use of a large-head toothbrush were not significantly reduced. PI measurements indicated significant reductions in dental plaque for both head types. However, detailed analysis by tooth surface revealed that the regular-sized toothbrush significantly reduced plaque on the proximal, palatal/lingual, and labial/buccal surfaces. In contrast, the large-head toothbrush only showed significant reductions in place on the proximal and palatal/lingual surfaces, not on the labial/buccal surface. Additionally, compared to the regular-sized toothbrush, the large-head toothbrush retained more toothpaste residue despite similar cleaning efforts after brushing. Conclusion: Compared to the regular-sized toothbrush, the large-head toothbrush showed lower overall efficacy in dental plaque removal. The results of this study provide significant information regarding the use of large-head toothbrushes.